METHOD OF LABORATORY ANALYSIS FOR OIL SHALE ASSAY - Herlan Adim (Scientific Contributions Oil and Gas, 2004)
Oil shale is much commoner than is generally realized, occuring on every continent and in every geological system. They are misnamed, but it is unlikely that any more appropriate name will be acceptable either to geologists. Few important deposits actually consist of shales and even fewer have yielded any oil. In the conventional sense most "oil shale" is actually bituminous, nonmarine limestones or marlstones containing kerogen. Only a few marine examples can be properly described as shales. The common composition involves about 50 percent of mineral carbonates by weight. A variety of silicates may also be present, possibly derived from the reaction of circulating alkaline waters with volcanic debris.